2013
DOI: 10.1084/jem.20112061
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial and dendritic cells in the thymic medulla promote CD4+Foxp3+ regulatory T cell development via the CD27–CD70 pathway

Abstract: CD27–CD70 signals are required for optimal development of natural regulatory T cells from the thymus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
126
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(140 citation statements)
references
References 76 publications
(124 reference statements)
12
126
1
1
Order By: Relevance
“…Therefore, CD27 signaling either improved the function of or enhanced the exhaustion and death of effector T cells, depending on the strength, duration, and timing of the agonistic stimulation (16,17,35,37). Additionally, slower tumor growth in CD27 2/2 mice due to diminished T reg numbers was reported, supporting the role of CD70-CD27 interaction in the generation and survival of T reg (38,39).…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Therefore, CD27 signaling either improved the function of or enhanced the exhaustion and death of effector T cells, depending on the strength, duration, and timing of the agonistic stimulation (16,17,35,37). Additionally, slower tumor growth in CD27 2/2 mice due to diminished T reg numbers was reported, supporting the role of CD70-CD27 interaction in the generation and survival of T reg (38,39).…”
mentioning
confidence: 78%
“…An additional concern arises from studies reporting that CD27 signaling favors T reg development or survival and that the absence of CD27 in CD27 2/2 mice leads to slower tumor growth compared with wild-type mice (38,39). It has also been reported that T reg from CD70 2/2 mice were reduced and not as efficient at suppressing CD4 Th cell proliferation compared with T reg from wild-type mice, suggesting a role for the CD70-CD27 interaction in maintaining T reg survival and function (59).…”
Section: Discussionmentioning
confidence: 99%
“…However, our data from in vitro culture of F5 thymocytes suggest the Tnfrsf ligands such as TNF and CD70 may be implicated. There is already evidence to suggest these ligands may be present in the thymus because TNF mRNA can be detected in dendritic cells ex vivo (32), and CD70 is already implicated in development of regulatory T cells in the thymus (33). Future studies should address whether these ligands alone are sufficient for induction of Il7r expression or whether other NF-κB-activating receptors may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…7B), possibly accounting for the upregulation of CD27 on CD4SP and CD8SP thymocytes in aly/aly mice. In this context, a recent report suggesting that mTECs, together with thymic DCs, promote Treg production via the CD27-CD70 pathway merits attention (44). The authors suggested that the CD27-CD70 pathway rescues developing Tregs from apoptosis.…”
Section: Foxp3mentioning
confidence: 99%